Application of the Project Based Learning Model to Improve Student Learning Outcomes - Yuyu Wahyudin (Beginner: Journal of Teaching and Education Management, 2023)
This research aims to examine the application of the Project Based Learning learning model to improve student learning outcomes. This research concludes that the application of the Project Based Learning learning model can improve student learning outcomes, because the project based learning model in any subject related to projects has an effect on student learning outcomes. Because students are actively involved when taking part in the learning. This learning model is where students not only understand a problem in learning but students are creative, innovative, and create projects as the final step. using problems as a first step in learning, aims to provide an understanding of critical thinking.